Proposta de centro de acolhimento a pessoas idosas em Belém- PA - JESUS, Ruan Lima de (2019)
The present work aims to develop the architectural design of a care center for the elderly. Thus, we seek to investigate which elements lead the elderly to need care in this type of institution. Topics such as social vulnerability and the architectural and design solutions that the institution will provide for the welfare of its residents, as well as its operating structure, will also be addressed. Our primary reference was the Our Home Socorro Gabriel, a long-term home located in Belém that currently has 80 elderly residents.